Interrupting a mitochondrial DNA–driven innate immune circuit attenuates hepatic tissue remodeling and fibrotic architecture in experimental steatohepatitis - Rabab S. Hamad; Sura Akram Mohammed; Waseem Ali Hasan; Norhan Ahmed AbuoHashish; Sherin Refat El Afify; Mohamed A.M. Ali; Alaa Eldin Ahmed Mohamed; Attalla F. El-kott; Mohammed A. AlShehri; Kareem Morsy; Alshaimaa A. Farrag; Karem Mohamed Salem; et al. (Tissue and Cell, 2026)

Mechanistic Insights into Honey-Mediated Antibacterial Activity Against Enterobacteriaceae: A Multifaceted Approach Targeting Membrane Integrity, Protein Synthesis, and Quorum Sensing Inhibition - Mervat G. Hassan; Naseh A. Algehainy; Batul Hatem Ghoniem; Faisal H. Altemani; Ashraf Elsayed; Hanaa Ghabban; Alaa Elmetwalli (Probiotics and Antimicrobial Proteins, 2026)

Taurine protects against gentamicin-induced neurotoxicity through dual modulation of Nrf2 and NF-κB pathways - Amira E. Farage; Medhat Taha; Basma Adel Khattab; Nawal E. Al-Hazmi; Alaa Eldin Ahmed Mohamed; Marwa M. Mona; Marwa M. Abd-Elsalam; Ahmed Elsayed Elsukary; Mohamed A.F.E. Sarhan; Ahmed shaban Abdelmonsef; Tourki A.S. Baokbah; Ibrahim El-Shenbaby; et al. (Tissue and Cell, 2026)

Toward Eco-Friendly Solutions for Plastic Pollution: Insights into Polyethylene Biodegradation - Alaa F. Elsayed; Dina H. Amin; Hassan M. Gebreel; Ihsan Mahasneh; HebatAllah I. Youssef (Water, Air, & Soil Pollution, 2026)

Uterine and ovarian hemodynamics assessment of Camelus dromedarius with hormonal alterations and anatomical and histological architecture - Elshymaa A. Abdelnaby; Asmaa M. Ibrahium; Aya M. Mekkawy; Ibrahim A. Emam; Alaa H. Elsayed (Veterinary Research Communications, 2026)

Biochemical and histological alterations induced by florpyrauxifen-benzyl herbicide in Nile tilapia (Oreochromis niloticus) - Noura Nabet; Elsayed A. Khallaf; Alaa Alnenaey; Islam M. El-Garawani; Esraa Hanafy; Nasr Khalil; Amany E. Nofal (Environmental Science and Pollution Research, 2026)

Chitosan reduces methane emissions and alters the phylogenetic affiliation of sampled methanogens in in vitro rumen fermentation - Marwa F. A. Attia; Amr E. El-Nile; Alaa M. A. Gad; Mohamed S. Moharam; Ahmed E. Kholif; Raed A. Aburawash; Elsayed E. Hafez; Sobhy M. A. Sallam (Environmental Science and Pollution Research, 2026)

Generic Gaidai multidimensional model for survival function, based on Arctic offshore wind measurements, using a novel log-integral extrapolation scheme - Oleg Gaidai; Shicheng He; Jinlu Sheng; Tanyaradzwa Kuzvidza; Ahmed Elkelity; Alaa Elsayed; Ahmed Alaghbari; Yan Zhu (Regional Studies in Marine Science, 2025)

Comparative morphometric, morphological, and radiographic studies of the mongrel and German shepherd dog mandibles with their clinical value for regional anesthesia - Reem R. Tahon; Alaa H. Elsayed (Zoomorphology, 2025)

Efficacy, safety and mechanistic insights of pentoxifylline in major depressive disorder: a systematic review and meta-analysis of randomized controlled trials - Omar Kassar; NourAllah Farag; Abdullah Selim; Lamees Taman; Menna Alaa; Ahmed Elshahat; Moaz Elsayed Abouelmagd (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Novel treatments that act beyond the conventionally targeted monoamine system are urgently needed to provide more effective relief for patients with major depressive disorder. Pentoxifylline (PTX) is a phosphodiesterase inhibitor with potent anti-inflammatory and antioxidant effects, with additional pleiotropic effects. This is the first systematic review and meta-analysis to examine the role of PTX in major depressive disorder. A comprehensive search of electronic databases, including PubMed, Scopus, Cochrane, and Web of Science, was performed in October 2024. We included only randomized controlled trials (RCTs), and their data were extracted and analyzed using Reman 5.4 software. The primary outcome was the change in Hamilton Depression Rating Scale (HAM-D). Four RCTs with 318 patients were included in the study. PTX showed a statistically significant improvement in HAM-D scores at the primary endpoint compared to the placebo (MD = –3.84, 95% CI [–4.87 to –2.81], P < 0.00001). Moreover, PTX showed a statistically significant increase in serotonin and BDNF levels (MD = 20.76 ng/mL, 95% CI [5.49 to 36.04], P = 0.008; and MD = 10.83 ng/mL, 95% CI [-0.22 to 21.88], P = 0.05, respectively) and a statistically significant decrease in TNF-α and IL-6 levels (MD = –3.24 pg/mL, 95% CI [–4.12 to –2.36], P < 0.00001; and MD = –2.64 pig/mL, 95% CI [–3.79 to –1.48], P < 0.00001, respectively). There was no statistically significant difference between the PTX and placebo in any of the reported side effects. The study findings suggest that PTX may be effective and safe as an adjuvant antidepressant agent in patients with MDD, demonstrating a significant reduction in HAM-D scores. The results of this study need to be interpreted with caution considering several limitations.

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

The induced hepatotoxicity and genotoxicity in Oreochromis niloticus exposed to a newly released florpyrauxifen-benzyl herbicide - Noura Nabet; Elsayed A. Khallaf; Alaa Alne-na-ei; Islam M. El-Garawani; Rehab G. Elgendy; Esraa Hanafy; Nasr Khalil; Heba M. R. Hathout (Ecotoxicology, 2025)
The investigation of the toxic potential of a newly introduced herbicide, Florpyrauxifen-benzyl (FPX), on Nile tilapia ( Oreochromis niloticus ) was the aim of this study. For 96 h, the median lethal concentration (LC 50 ) was assessed in fish juveniles using the Probit analysis following the exposure to five concentrations of FPX (2–3 ppm). For investigating some mechanisms of FPX toxicity, fish were allocated into three groups (0, 0.27 and 0.54 ppm of FPX) and the cut-off intervals of the exposure were at 7 and 15 days. Liver malondialdehyde (MDA) and reduced glutathione (GSH) levels were assessed. In addition, superoxide dismutase (SOD) and catalase (CAT) were evaluated at both of transcriptional and enzymatic activity levels. Histopathological effects on the liver and erythrocytic nuclear abnormalities (ENAs) were monitored too. The 96h-LC 50 was found to be 2.61 ppm, revealing the toxic potential of the FPX on Nile tilapia. Concentrations of FPX induced oxidative stress in fish by altering activities of antioxidant enzymes and their transcripts. The genotoxic effect of FPX was evidenced by a significant ( P < 0.05) increase in micronuclei (MNs) and ENA frequencies. Significant liver histopathological alterations were observed at both FPX concentrations, with the highest effects at a concentration of 0.54 ppm FPX. Results suggest that FPX may exert oxidative, genotoxic, and histopathological effects on non-targeted species such as Nile tilapia if it is used improperly. Although fish could be used as an indicator for toxic materials in the aquatic habitat, future studies on other organisms, FPX concentrations or durations are recommended.

Harnessing the power of miRNAs for precision diagnosis and treatment of male infertility - Ahmed S. Doghish; Elsayed G. E. Elsakka; Hebatallah Ahmed Mohamed Moustafa; Alaa Ashraf; Sherif S. Abdel Mageed; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Mohamed Bakr Zaki; Hanan Elimam; Nehal I. Rizk; Sarah A. Omran; Shimaa A. Farag; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Mesoporous magnetic biochar derived from common reed (Phragmites australis) for rapid and efficient removal of methylene blue from aqueous media - Wael Ibrahim Mortada; Mahmoud Mohsen Ghaith; Nada Elsayed Khedr; Mostafa Ibrahim Ellethy; Alaa Waleed Mohsen; Amira Labib Shafik (Environmental Science and Pollution Research, 2024)
A novel mesoporous magnetic biochar (MBC) was prepared, using a randomly growing plant, i.e., common reed, as an exporter of carbon, and applied for removal of methylene blue (MB) from aqueous solutions. The prepared sorbent was characterized by nitrogen adsorption/desorption isotherm, saturation magnetization, pH of point of zero charges (pH PZC ), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The obtained MBC has a specific surface area of 94.2 m 2 g −1 and a pore radius of 4.1 nm, a pore volume of 0.252 cm 3 g −1 , a saturation magnetization of 0.786 emu g −1 , and a pH PZC of 6.2. Batch adsorption experiments were used to study the impact of the physicochemical factors involved in the adsorption process. The findings revealed that MB removal by MBC was achieved optimally at pH 8.0, sorbent dosage of 1.0 g L −1 , and contact time of 30 min. At these conditions, the maximum adsorption was 353.4 mg g −1 . Furthermore, the adsorption isotherm indicated that the Langmuir pattern matched well with the experimental data, compared to the Freindlich model. The ∆ G was − 6.7, − 7.1, and − 7.5 kJ mol −1 , at 298, 308, and 318 K, respectively, indicating a spontaneous process. The values of ∆ H and ∆ S were 5.71 kJ mol −1 and 41.6 J mol −1 K −1 , respectively, suggesting endothermic and the interaction between MB and MBC is van der Waals type. The absorbent was regenerated and reused for four cycles after elution with 0.1 mol L −1 of HCl. This study concluded that the magnetic biochar generated from common reed has tremendous promise in the practical use of removing MB from wastewater. Graphic Abstract

Antioxidant and anti-inflammatory potential of spirulina and thymoquinone mitigate the methotrexate-induced neurotoxicity - Alaa Behairy; Ashraf Elkomy; Faten Elsayed; Mohamed M. S. Gaballa; Ahmed Soliman; Mohamed Aboubakr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The objective of this study was to investigate whether the neurotoxic effects caused by methotrexate (MTX), a frequently used chemotherapy drug, could be improved by administering Spirulina platensis (SP) and/or thymoquinone (TQ). Seven groups of seven rats were assigned randomly for duration of 21 days. The groups consisted of a control group that was given saline only. The second group was given 500 mg/kg of SP orally; the third group was given 10 mg/kg of TQ orally. The fourth group was given a single IP dose of 20 mg/kg of MTX on the 15 th day of the experiment. The fifth group was given both SP and MTX, the sixth group was given both TQ and MTX, and the seventh group was given SP, TQ, and MTX. After MTX exposure, the study found that AChE inhibition, depletion of glutathione, and increased levels of MDA occurred. MTX also decreased the activity of SOD and CAT, as well as the levels of inflammatory mediators such as IL-1, IL-6, and tumor necrosis factor-α. MTX induced apoptosis in brain tissue. However, when MTX was combined with either SP or TQ, the harmful effects on the body were significantly reduced. This combination treatment resulted in a faster return to normal levels of biochemical, oxidative markers, inflammatory responses, and cell death. In conclusion, supplementation with SP or TQ could potentially alleviate MTX-induced neuronal injury, likely due to their antioxidant, anti-inflammatory, and anti-apoptotic effects.

Di (2-ethylhexyl) phthalate alters neurobehavioral responses and oxidative status, architecture, and GFAP and BDNF signaling in juvenile rat's brain: Protective role of Coenzyme10 - Naglaa Z.H. Eleiwa; Alaa S.F. Elsayed; Enas N. Said; Mohamed M.M. Metwally; Yasmina M. Abd-Elhakim (Food and Chemical Toxicology, 2024)

Salinity stress and different types of nano silicon's effects on lupine morphology and biochemical accumulations - Faten S.A. Zaki; Alaa E. Elsayed; Aisha M.A. Ahmed; Khalid A. Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Novel green HPTLC and organic solvent-free micellar LC methods for the simultaneous determination of Ozenoxacin and benzoic acid; greenness assessment and applications - Adel Ehab Ibrahim; Mohamed Farouk Taher; Alaa El Gindy; Elsayed A. Ibrahim (Sustainable Chemistry and Pharmacy, 2023)

Usage of natural wastes from animal and plant origins as adsorbents for the removal of some toxic industrial dyes and heavy metals in aqueous media - Afnan S. Batubara; Hamad M. Adress Hasan; Mohammed A. Abel Moniem; Mamdouh S. Masoud; Alaa-Eldin R. Mostafa; Mohammed Gamal; Mohamed A. Elsayed (Journal of Water Process Engineering, 2023)

Correction to: Potentials of mono‑ and multi‑metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)

Potentials of mono- and multi-metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)
In this work, cotton stalks ( Gossypium barbadense ) and date palm stones ( Phoenix dactylifera ) have been used as biosorbents to remove cadmium; Cd(II), lead; Pb(II), and zinc; Zn(II) from mono- and multi-solutions. Each biosorbent was characterized using SEM-EDX, and FT-IR. The findings showed that pH, dose, contact time, metal concentration, and particle size affect the treatment process. The adsorption pattern was Pb(II) > Cd(II) > Zn(II) for both biosorbents. The adsorption performance of cotton stalks was higher than that of date palm stones. The fitted maximum uptake capacities; q m of cotton stalks were higher than those of date palm stones. The maximum adsorption at optimum conditions of Pb(II), Cd(II), and Zn(II) with cotton stalks were 98%, 92.1%, and 78.9%, respectively, within 30 min. While the maximum adsorption of Pb(II), Cd(II), and Zn(II) with date palm stones were 94.6%, 76%, and 68.6%, respectively. Results confirmed the antagonistic effect of heavy metal removal at optimum conditions. Biosorbents could remove ~ 100% of the metal ions from real wastewater samples. Regeneration investigation revealed a successful reusability of both biosorbents for four cycles.

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials - Mohamed Sayed Zaazouee; Mahmoud Eleisawy; Amira M. Abdalalaziz; Mahmoud M. Elhady; Omar Adel Ali; Taghreed Mohamed Abdelbari; Sara Mohamed Hasan; Hossam Waleed Almadhoon; Alaa Yehia Ahmed; Alaa Shaban Fassad; Rewan Elgendy; Eman Adnan Abdel-Baset; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19. Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywords/Mesh terms. Only randomized clinical trials (RCTs) that addressed the topic were included. The Cochrane tool was used to assess the studies’ risk of bias, and the data were analyzed using the review manager (RevMan 5.4). We included nine RCTs with 1586 confirmed COVID-19 patients. Vitamin D group showed a significant reduction of intensive care unit (ICU) admission (risk ratio = 0.59, 95% confidence interval (CI) [0.41, 0.84], P = 0.003), and higher change in vitamin D level (standardized mean difference = 2.27, 95% CI [2.08, 2.47], P < 0.00001) compared to the control group. Other studied hospital and laboratory outcomes showed non-significant difference between vitamin D and the control group ( P ≥ 0.05). In conclusion, vitamin D reduced the risk of ICU admission and showed superiority in changing vitamin D level compared to the control group. However, other outcomes showed no difference between the two groups. More RCTs are needed to confirm these results.

The Effect of Neonicotinoids Exposure on Oreochromis niloticus Histopathological Alterations and Genotoxicity - Islam M. El-Garawani; Elsayed A. Khallaf; Alaa A. Alne-na-ei; Rehab G. Elgendy; Hassan M. Sobhy; Adel Khairallah; Heba M. R. Hathout; Farag Malhat; Amany E. Nofal (Bulletin of Environmental Contamination and Toxicology, 2022)
This study aimed to examine the side effects of selected neonicotinoids (Acetamiprid, Aceta, and Imidacloprid, Imid) on Oreochromis niloticus juveniles. The acute toxicity, Probit method, revealed an LC 50 of 195.81 and 150.76 ppm for Aceta/96 h and Imid/72 h respectively. The fish were divided into three groups that were exposed, for 21 days (n = 5/replicate), to 1/10 of the LC 50 of either neonicotinoids, however, the third was an unexposed control group. Results of erythrocytic micronucleus (MN), and nuclear abnormalities (NA) showed that Aceta and Imid exposure caused a significant ( p < 0.05) increase in MN by ~ 2.2 and ~ 10 folds, respectively relative to control. NAs occurred at the order of kidney-shaped > budding > binucleated in Aceta, however, budding > binucleated > kidney-shaped was noticed in the Imid group. Histopathological changes in gills, liver, and muscles were observed significantly in both exposed groups with more severity in the Imid group. Collectively, Aceta and Imid have potential genotoxicity and histopathological alterations in O. niloticus .

Expression profiling of HSP 70 and interleukins 2, 6 and 12 genes of Barki sheep during summer and winter seasons in two different locations - Raed A. Abu Rawash; Mahmoud A. Sharaby; Gamal El-Din A. Hassan; Alaa E. Elkomy; Elsayed E. Hafez; Salma H. Abu Hafsa; Mohamed M. I. Salem (International Journal of Biometeorology, 2022)
The objectives of this research were to contrast the expression values of heat shock protein (HSP70) and interleukins 2, 6 and 12 (IL 2, IL 6 and IL 12) genes in summer and winter in two different locations in Egypt (Alexandria zone and Matrouh zone) to deduce changes in thermo-physiological traits and biochemical blood metabolites of Barki sheep. A total of 50 ewes (20 in Alexandria and 30 in Matrouh) were individually blood sampled to determine plasma total protein (TP), Albumin, Globulin and Glucose constituents and T3, T4 and cortisol hormones. The thermo-physiological parameters of rectal temperature (RT, °C), skin temperature (ST, °C), Wool temperature (WT, °C), respiration rate (RR, breaths/min) and pulse rate (PR, beats/min) were measured for each ewe. Expressions of IL 2, IL 6, IL 12 and HSP 70 in summer and winter were analyzed along with thermo-physiological parameters and blood biochemical metabolites. In both locations, THI had significant effects on ST, WT, PR and RR, but not significant on RT. However, it had no significant effects on blood plasma metabolites and hormonal concentrations in the two locations in summer and winter. In Alexandria location, THI had negative significant effect on the expressions of IL-2 and IL-6 but positively affected on HSP70 genes in winter, while the expression of IL-12 gene was not affected by seasons, whereas in Matrouh zone, the effects of THI on the expressions of all tolerance genes were not significant. The results of the current study suggest that IL-2, IL-6 and HSP70 genes could be used as molecular markers for heat/cold stress.

Propagation of the Multi-Scalar Aggregative Standardized Precipitation Temperature Index and its Application - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Dost Muhammad Khan; Rizwan Niaz; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry (Water Resources Management, 2020)

Measuring the ecological footprint of inbound and outbound tourists: evidence from a panel of 35 countries - Muhammad Imran Qureshi; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry; Alamzeb Aamir; Nik Hasnaa Nik Mahmood; Amran Md. Rasli; Khalid Zaman (Clean Technologies and Environmental Policy, 2019)

Contamination and Ecological Hazard Assessment of Heavy Metals in Freshwater Sediments and Oreochromis niloticus (Linnaeus, 1758) Fish Muscles in a Nile River Canal in Egypt - Elsayed A. Khallaf; Mohammad M.N. Authman; Alaa A. Alne-na-ei (Environmental Science and Pollution Research, 2018)

The changing patterns of bladder cancer in Egypt over the past 26 years - Ashley S. Felix; Amr S. Soliman; Hussein Khaled; Mohamed S. Zaghloul; Mousumi Banerjee; Manal El-Baradie; Mohamed El-Kalawy; Alaa A. Abd-Elsayed; Kadry Ismail; Ahmed Hablas; Ibrahim A. Seifeldin; Mohamed Ramadan; et al. (Cancer Causes & Control, 2008)